Potential nutritive value of Trigonella spicata hay harvested at different maturity stages - Uslu, Omer Suha (Progress in Nutrition, 2021)
The aim of the current experiment was to determine the effects of harvesting maturity on the chemical composition, dry matter digestibility (DMD), dry matter intake (DMI) and relative feed value (RFV), gas production, methane production, metabolisable energy (ME) and organic matter digestibility (OMD) of Trigonella spicata hay. Harvesting maturity had a significant (P<0.001) effect on chemical composition, DMD, DMI and RFV, gas production, methane production, ME and OMD of Trigonella spicata hay. Crude protein (CP), ether extract (EE), DMD, DMI and RFV, gas production, methane production, ME and OMD of Trigonella spicata hay decreased with increasing maturity whereas the cell wall contents (NDF and ADF) increased with increasing maturity. In conclusion, maturity had a significant effect on the nutritive value of Trigonella spicata hay. It seems to reasonable that Trigonella spicata hay will provide more nutrient to ruminant animals when harvested or grazed at preflowering and flowering stages.